Influence of contact parameters on material transfer from steel to TiN coated tool – optimisation of a sliding test for simulation of material transfer in milling. (2nd July 2016) - Aiso, Toshiharu; Wiklund, Urban
Abstract : Sliding between crossed cylinders, one large work material cylinder and one smaller coated tool cylinder, can be used to simulate the contact between a chip and the rake face of a cutting tool. However, accurate simulations require the mode of material transfer in the test to match that in real machining. The mode is strongly dependent on normal load and sliding speed, and it is classified into four types; negligible oxide, only iron oxide, iron oxide and alloy oxide, and metallic transfer with coating cracking. A high load proved to be the most important to accurately simulate the mode and area of material transfer occurring in milling. The diameter of the work material cylinder influences the shape of the contact mark, but has no influence on the mode of transfer. This means smaller work material diameters can favourably be used, reducing costs and facilitating handling during both tests and analysis.